THE SUSCEPTIBILITY TESTING OF MUCOR AND ASPERGILLUS SPP. TO SOME PLANT ORIGIN SUBSTANCES - Передера, С. Б.; Кінаш, О. В. (Scientific Progress & Innovations, 2015)
The results of susceptibility testing of Aspergillus and Mucor to plant origin substances (infusion of Echinacea purpurea, Echinacea liquid extract, Echinacea tincture, essential oil of Basil, essential oil of Monarda, eugenol) are shown. There are numerous data in the literature relating to bactericidal and immunostimulatory activity of those substances, however, the data for their fungicidal properties described insufficiently. The studies was conducted by standard disc-diffusion method. We used medications of Echinacea purpurea and essential oils of pharmaceutical network. Plant origin substances are promising for use in veterinary medicine as an alternative to antibiotics and disinfectants simultaneously. In particular, essential oils and their components can be used to optimize the air of poultry premises, as a disinfectant and as chemicals of anabolic and immunostimulatory action.